PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (Student Teams Achievement Division) UNTUK MENINGKATKAN HASIL BELAJAR KIMIA POKOK BAHASAN LAJU REAKSI PADA SISWA KELAS XI IPA SMA NEGERI 7 PALU - Angriani, Eva; Tiwow, Vanny M.A.; Tangkas, I Made (Universitas Tadulako, 2013)
The research was conducted at SMAN 7 Palu for the purpose to improving student learning outcomes of Chemistry through the use of Cooperative Learning Type STAD methods (Student Teams Achievement Division) on the chemistry subject of reaction rate. Population of this research was all students in class XI IPA SMA Negeri 7 Palu academic year 2012/2013, consisting of 3 classes. The sample were in class XI IPA 2 with total 34 students, as the experimental class that used cooperative learning STAD method and class XI IPA 1 with total 37 students as a control class (not used Cooperative learning STAD methods). The data were collected by using the test instrument. The data collecting result use the statistical analysis t-test with the prerequisite test for normality and homogeneity tests. The study shows that the mean value of student learning outcomes use cooperative learning STAD model is 7.66; the mean value of student learning outcomes without using cooperative learning STAD model was 5.57. Based on the hypothesis testing using statistical t-test in the right side earned value thitung > ttabel is 5.36 > 1.66 with degree of freedom = 0.05 and dk = 69. The results shows that the use of cooperative learning STAD model could improve learning outcomes of students in reaction rate of chemistry subject.